Pengaruh Good Corporate Governance, Kinerja Keuangan, Dan Struktur Modal Terhadap Nilai Perusahaan - Ayu Rida Amanah; Mudzakir Mudzakir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of good corporate governance, financial performance, and capital structure on firm value in an empirical study of healthcare sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. The sampling technique used purposive sampling. The sample resulted in 13 companies listed on the IDX for 4 (four) years with a total of 52 observations of financial report data. The hypothesis testing method in this study was tested using descriptive statistical analysis and regression analysis using the Eviews-13 program. The results of this study partially test good corporate governance has no effect on firm value, financial performance has a significant effect on firm value, and capital structure has no effect on firm value. Simultaneously, good corporate governance, financial performance, and capital structure influence the value of healthcare sector companies listed on the Indonesia Stock Exchange for the period 2021-2024.